Literature review Factors Influencing Preconception Screening in Indonesia. - Kusumawardani , Paramitha Amelia (International Journal Multidisciplinary (IJMI), 2024)
To obtain good preconception health, preconception screening is needed for women of childbearing age and couples of childbearing age. Preconception screening is beneficial and has a positive effect on the health preparation of the mother and the prospective child so that later the pregnancy can run well and healthily. The purpose of the study was to determine the factors that influence preconception screening. The research method used was a literature review with a Narrative Review design. The results based on 3 studies showed that education and knowledge factors are quite strong factors and have a positive variable direction that influences preconception screening. Age, attitude, husband's support, health worker information and culture are other influencing factors. The conclusion of the factors influencing preconception screening is that education, knowledge, age, attitude, husband's support, health worker information and culture are factors that influence preconception screening.